Probing the effect of intragranular premature κ-carbide on incipient plasticity behavior in austenite-based Fe-Mn-Al-(Cr)-C steels. Issue 3 (4th March 2022) - Zhang, Jianlei; Liu, Yuxiang; Hu, Conghui; Addad, Ahmed; Montagne, Alex; Ji, Gang; Song, Changjiang; Zhai, Qijie
Abstract : The effect of nanoscale intragranular premature κ-carbide precipitates, having an ordered structure but without chemical partitioning, on the incipient plasticity behavior of austenite in Fe-Mn-Al-(Cr)-C low-density steels was investigated by nanoindentation. We found that the incipient plasticity was dominated by a heterogeneous dislocation nucleation mechanism via atom-vacancy exchange. Although the content of κ-carbide decreased with Cr addition, its negligible effect on incipient plasticity strength was witnessed by the slightly increased shear stress for dislocation nucleation. Comparatively, the increased interstitial C atoms with Cr content in austenite enhanced lattice cohesions which impeded the nucleation events by increasing the requisite shear stress. GRAPHICAL ABSTRACT: UF0001 IMPACT STATEMENT: Despite being one of the most important strengthening phases, nanoscale premature κ-carbide precipitates surprisingly have a negligible effect on incipient plasticity of austenite in Fe-Mn-Al-(Cr)-C low-density steels.